Pengembangan Aplikasi E-Assessment Berbasis Passing Grade Menggunakan Pendekatan Agile Software Development - Irmansyah Lubis, Ahmadi (TIN: Terapan Informatika Nusantara, 2025)
In the digital era, the use of technology in learning evaluation is a necessity to improve the efficiency and objectivity of assessment. This research aims to develop a passing grade-based e-assessment application that allows automatic assessment of student exam results. The system is designed to provide real-time feedback and increase transparency in the academic evaluation process. Application development is carried out using the Agile Software Development approach, which allows for iterative software development with continuous updates based on user feedback. The case study was conducted in the Software Engineering Technology Study Program at the Batam State Polytechnic to test the effectiveness of the system in improving the quality of learning evaluation. The test results show that this application is able to increase the efficiency of the assessment process by reducing the time of manual exam correction and increasing accuracy in grading. Then the passing grade system helps students to understand the achievement of their competencies more clearly and encourages them to improve their understanding of lecture materials. With the implementation of this application, it is hoped that educational institutions can adopt a more flexible and adaptive technology-based evaluation system. The results of this research can be used as a reference in the development of e-assessment systems in other academic environments.